Effect of Non-hormonal Treatments on Postpartum True Anoestrus Crossbred Dairy Cows - Bora, Bhaskar; Perumal, P.; Bonia, K. K.; Biswas, R. K. (International Journal of Bio-resource and Stress Management, 2023)
The present study was conducted to study the efficacy of different medicaments on postpartum anoestrus crossbred cows. Total of 20 post partum anoestrus crossbred cows were selected based on the case history and rectal palpation from the private dairy farm in and around the Khanapara, Guwahati, Assam. The animals were split into two groups (n=10) and treated with Vitamin A+Tonophosphan (Group 1), Vitamin A+Tonophosphan+Genital Massage (Group 2). Result of experiment revealed that number of animal responded and conceived were higher and duration between the initiation of treatment and expression of heat was shorter in group 2 treatment and expression of various heat signs were more prominent in this group 2 treatment. Similarly the biochemical profiles were higher in responded animal than non- responded and in group 2 treatment. Moreover, the biochemical profiles were significantly higher in day of induced oestrus, day 20 than day 10 or 0 of treatment in responded animal and higher in group 2 treatment. It was concluded that group 2 (Vitamin A+Tonophosphan+Genital Massage) treatment was given better response to the postpartum anoestrus in crossbred cows.